Cost-effectiveness analysis of continuous venovenous hemofiltration therapy in the treatment of sepsis in Hospital Universiti Kebangsaan Malaysia: a comparison between high volume and standard dose hemofiltration - A M Rizal,; M H Enna,; S M Aljunid,; A G Rohana,; Z Soehardy,; C T K Norella, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Background: A randomised clinical trial was carried out to study the cost-effectiveness of continuous venovenous hemofiltration using high volume and standard volume. Methods: Study was done through interviews involving patients or their relatives and document review on patients’ treatment and progress note during the hemofiltration therapy in the Intensive Care Unit, Hospital University Kebangsaan Malaysia. Study also involved secondary data analysis and a structured questionnaire survey to assess the treatment and medical cost incurred by the hospital during the continuous venovenous hemofiltration therapy. Results: The result of this study showed that the continuous venovenous hemofiltration given at high volume 4-6 litres/hour is more cost effective than standard volume of 2 litres/hour. The Sequential Organ Failure Assessment (SOFA) score reduction in the high volume hemofiltration is 3.0 units over 24 hours. This reduction is higher than the standard volume hemofiltration which is only 0.5 unit over 24 hours. Conclusions: High volume hemofiltration is more cost effective than standard volume therapy, where only RM 5,552 compared to RM 23,512 is needed for every one unit of SOFA score reduction respectively.